Plan de mantenimiento preventivo para los vehículos de transporte privado de la empresa Palmeras del Puerto S.A.S (2022)
In the municipality of Puerto López, Meta; The private personnel transportation company Palmeras del Puerto is located, the company has been providing the service for several years to agro-industrial and oil companies (Bioenergy, Riopaila, Upecol, Ecopetrol etc.) that are located in the area. These companies have their facilities in the rural area of the municipality, therefore the routes tend to be in non-optimal conditions for the transport system and due to the poor condition of the access roads, a series of technical-mechanical problems arise. in vehicles. With respect to this situation, there have been multiple failures, causing the vehicles to not be able to finish their established routes, many times being stranded even with personnel on board. The company has not taken action on the matter and only performs corrective maintenance when these incidents occur. That is why preventive maintenance should be carried out, taking into account the wear of the vehicle from a weekly record of the mileage per vehicle.